Mass-produced romance: BookTok society and the homogenisation of literary culture - Anggie Ayu Isra Tristanty; Johny Alfian Khusyairi (Jurnal Studi Komunikasi, 2025)
This study examined how BookTok reinforces literary homogenisation through algorithm-driven virality, applying Adorno's concept of the culture industry. Analysis of survey data shows that 78% of users frequently encounter repetitive tropes, such as ‘Enemies to Lovers’ and ‘Fake Dating’, while 66% report that these patterns influence their reading choices. Additionally, over 70% of viral BookTok recommendations promote mass-market romance novels, mainly works by bestselling authors such as Colleen Hoover and Emily Henry. In contrast, books with experimental narratives or by underrepresented authors remain marginalised. BookTok's algorithm amplifies high-engagement content, creating a self-perpetuating cycle of popularity that aligns with Adorno's critique of cultural standardisation. This study highlights how BookTok prioritises commercial viability over literary diversity, narrowing reader exposure. However, this trend could be reversed by intentional interventions like influencer-led book marketing and algorithmic changes. This study highlights BookTok's significance in influencing reading habits and highlighting ways to promote literary diversity by connecting the platform's influence to more extensive discussions on digital literary consumption.